Arm explosive power, hand–eye coordination, and motor ability in students' badminton lob performance - Asep Rizal; Ahmad Chaeroni; Eval E Edmizal; Sefri Hardiansyah (Journal of Educational and Learning Studies, 2026)
This study examined the direct and indirect effects of arm muscle explosive power, hand–eye coordination, and motor ability on badminton lob performance among athletes at the UNP Badminton Academy. A quantitative causal-correlational design was employed involving 12 athletes selected through total sampling. Standardized field tests measured all variables, and path analysis was performed after confirming normality, linearity, and multicollinearity assumptions. Arm muscle explosive power (β = 0.393, p = 0.020), hand–eye coordination (β = 0.430, p = 0.010), and motor ability (β = 0.484, p = 0.005) significantly improved lob performance, whereas indirect effects through motor ability were not significant. The model explained 88.7% of the variance in lob performance (R² = 0.887). Motor ability was the strongest predictor, while physical capacities contributed independently. These findings support integrated evidence-based training emphasizing explosive power, coordination, and motor ability to optimize badminton lob performance.